A NOVEL BIOMARKER RENALASE AND ITS RELATIONSHIP WITH ITS SUBSTRATES IN SCHIZOPHRENIA - Catak, Zekiye; Kocdemir, Esra; Ugur, Kader; Yardim, Meltem; Sahin, Ibrahim; Kaya, Hilal; Aydin, Suleyman (Sciendo, 2019)
Background: Schizophrenia, particularly the form related to excessive dopamine (DA), is a chronic psychotic disorder affecting millions of people worldwide. Renalase metabolizes its catecholamine (CA) substrates, including DA, suggesting that there might be an association between renalase levels and schizophrenia occurrence. Therefore, the current study aimed to evaluate the renalase and CA levels in the serum of patients with schizophrenia. Methods: The study was conducted with thirty-three schizophrenia patients and an age- and gender-matched group of thirty-one controls. Renalase and CA levels were measured by using an enzyme-linked immunosorbent assay (ELISA). Results: Renalase levels were significantly lower in the schizophrenia patients than in the control group (p <0.05), whereas DA levels were significantly higher (p<0.05). The epinephrine (Epi) levels of both groups were similar (p=0.186), while the norepinephrine levels in patients with schizophrenia were significantly lower than those in the control group (p<0.05). The areas under the curves for the renalase-dopamine, renalase-norepinephrine and renalase-epinephrine ratios were 0.805, 95% confidence interval (CI): 0.699-0.912 (p<0.001); 0.726, 95% CI: 0.594-0.859 (p=0.032); and 0.656, 95% CI: 0.520-0.791 (p=0.02). Conclusions: The high DA levels in patients with schizophrenia might be due to low renalase levels. Renalase enzyme levels may play a substantial role in the pathophysiology of schizophrenia. Thus, this enzyme might be a new future target for the treatment and diagnosis of schizophrenia after intrabrain renalase and DA dynamics have been further evaluated.
Keywords: catecholamine; dopamine; renalase; schizophrenia